Conditions of Stress Corrosion Crack Growth and Retardation in X70 Steel in Carbonate Environments - Ivo Cerny; Dagmar Mikulova; Pavel Novak (Communications - Scientific letters of the University of Zilina, 2010)
X70 steel has been often used for building of high pressure transit pipelines. In spite of multiple pipeline protection being used, namely insulation and cathodic protection, in complicated soil and environmental conditions, some pipeline sections can be exposed to corrosive environments. Seriousness of stress corrosion cracking (SCC) damage in carbonate environments is being sometimes flouted by some operators. The work was aimed at qualitative and quantitative analyses of SCC process and damage mechanisms under static loading with individual unloading cycles in standard carbonate solution at room and elevated temperatures. SCC growth was demonstrated as well as an importance of stress fluctuations affecting the process.